Calcium Silicate as a Media For Enhancement of Vitamin E Concentration from Candlenut Oil (Aleurites moluccana) - Sebayang, Firman; Surbakti, Merais Pana Br (Talenta Publisher, 2022)
Vitamin E consists of two parts, namely tocopherol and tocotrienol which are found as minor components in candlenut oil. The process of increasing vitamin E concentrate in candlenut oil aims to obtain higher vitamin E levels from candlenut oil through a major and minor component separation with adsorption and desorption methods with three types of calcium silicate hydrate adsorbent namely calcium silicate with 90% absolute ethanol (Ca-S 90), calcium silicate with 75% absolute ethanol (Ca-S 75) and calcium silicate synthesized from CaO (Ca-S). The three adsorbents were synthesized by hydrothermal method at 170ÂºC for 24 hours accompanied by stirring and characterized by XRD, SEM-EDX, and BET. Furthermore, the adsorbent was applied to enrich vitamin E concentrate in candlenut oil through the adsorption process using a glass column with a mass ratio between candlenut oil and adsorbent that was 1:1, then the vitamin E desorption process was carried out by adding n-hexane solvent. Vitamin E levels obtained after the adsorption and desorption process were for Ca-S 75 adsorbent was 764.41 ppm (1. 82 times enriched), for Ca-S 90 adsorbent was 1011.29 ppm (2. 40 times enriched) and for Ca-S adsorbent was 1029, 38 ppm (2.4 5 times enriched) from the initial vitamin E level in candle nut oil was 420.66 ppm. Ca-S adsorbent showed the best vitamin E enrichment.